2021
DOI: 10.3390/w13081039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature and Glyphosate on Fatty Acid Composition, Antioxidant Capacity, and Lipid Peroxidation in the Gastropod Lymneae sp.

Abstract: Little is known about the potential effects of glyphosate on freshwater gastropods and possible interactions between glyphosate and other stressors. A two-way factorial experiment was conducted to investigate the effects of temperature (20 °C/25 °C) and glyphosate (0 µg/L/200 µg/L) on Lymnaea sp. After 21 days, antioxidant capacity (superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) and glutathione-S-transferase (GST)), malondialdehyde content (MDA), and fatty acid (FA) composition of Lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…Even though temperature did not have a significant effect on SFA level, the CTR mussels at 26° C had a slightly higher SFA content. This is in accordance with results reported by Fadhlaoui and Lavoie [ 36 ] in a similar study on the effects of temperature and Gly on FA composition of the gastropod Lymneae sp. One explanation could be an adaptive response to maintain the structural rigidity of the cell membrane in these conditions [ 34 , 37 ].…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Even though temperature did not have a significant effect on SFA level, the CTR mussels at 26° C had a slightly higher SFA content. This is in accordance with results reported by Fadhlaoui and Lavoie [ 36 ] in a similar study on the effects of temperature and Gly on FA composition of the gastropod Lymneae sp. One explanation could be an adaptive response to maintain the structural rigidity of the cell membrane in these conditions [ 34 , 37 ].…”
Section: Resultssupporting
confidence: 93%
“…It can affect the physiology of organisms and their metabolic rates, as well as the toxicity of contaminants. In a similar study, Fadhlaoui and Lavoie [ 36 ] reported a different trend showing a decrease in oleic acid at the highest temperature. However, Cohen [ 59 ], in a study on the effects of the herbicides on FAs, reported an increase in oleic acid in one cyanobacterium and one marine microalga, thus indicating an inhibitory effect of the herbicide on the Δ6-desaturation system.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…This imbalance promotes oxidation that results in structural modification of biomolecules, such as carbohydrates, lipids, proteins and nucleic acids, consequently causing cellular alterations that can lead to high levels of inflammation and even cell death [ 78 , 79 , 80 ]. GBHs confer cytotoxic and genotoxic effects, increase oxidative stress, alter the immune system, impair some brain functions and are, supposedly, correlated with the development of some types of cancer [ 71 , 72 , 81 , 82 , 83 , 84 ]. In our study, the positive control (copper sulphate) behaved as expected [ 85 , 86 ], increasing the levels of ROS, NO and cell death in WT larvae.…”
Section: Discussionmentioning
confidence: 99%